(untitled) (RuMoRes, 2013)
Thisarticle, based onliterature review, reflecton howdigitalambiencescan enlargespacesof citizenshipthrough community radios. Therefore, we presentthe concept ofpublic relations community,confronting thelegislation oncommunity radio. In the end, we raise questionsabout hegemonic discoursesof technologyand howthat speechinterferesin the relationsbetween subjectsand digital media. We believe that thenew territoriality of thecommunity radios has great potential to be developed because of otherissues discussed – such as access andtraining subjects – beyondmedia education.